KONSUMERISME, VISI HIDUP, DAN PENDIDIKAN DALAM KELUARGA - BASWEDAN, ALIYAH RASYID (Universitas Negeri Yogyakarta, 2002)
Abstract University students are specific group of youth who are expected to become the driving force of the future development of the nation. Therefore, they have to be will qualified persons with product oriented culture, in order to transform the culture to be positive. This study examined the students’ lifestyle; to find out whether it was more product or consumption oriented. Specifically this study examined the consumerism tendency of the UNY students, and to find out whether their family education and their live vision had significant contribution to the students’ consumerism. The data indicated that : (1) the consumerism of the UNY students were not high, (2) the mothers’ role was more dominant that the fathers’ in reducing the students consumerism, and (3) the students who had clear life vision were at low consumerism. Keywords: university student, consumerism